Let's use the point-slope formula to write the equation of this line.
The point-slope formula is y - y₁ = m(x - x₁).
In the formula, x₁ and y₁ are points and the m is our slope
Now let's substitute.
y + 2 = -3/2(x - 6).
Notice that I put y + 2 above since y - (-2) means y + 2.
Now distribute the -3/2 through the parentheses.
This gives us -3/2x + 9.
Bring down your y + 2 and we have y + 2 = -3/2x + 9.
To put this in standard form, we need to multiply both
sides by 2 because we can't have any fractions.
This gives us 2y + 4 = -3x + 18.
Now move the +4 to the right by subtracting
4 from each side to get 2y = -3x + 14.
Now move your x term to the right by adding 3x to both sides.
So our final answer reads 3x + 2y = 14.